Project management : - Meredith, Jack R (Wiley, 2010)
This book makes learning Project management difficult. It does not clearly define anything. It is full of endless (and senseless) babble and author's "opinions" very few facts. I fully believe this is a required text because of the website Wiley created and the "bonus" cd of Project 2002